Debated agronomy: public discourse and the future of biotechnology policy in Ghana. Issue 1 (1st January 2017) - Braimah, Joseph A.; Atuoye, Kilian N.; Vercillo, Siera; Warring, Carrie; Luginaah, Isaac
ABSTRACT: This paper examines the highly contested and ongoing biotechnology (Bt) policy-making process in Ghana. We analyse media content on how Bt is viewed in the context of Ghana's parliamentary debate on the Plant Breeders Bill and within the broader public policy-making literature. This paper does not seek to take a position on Bt or the Bill, but to understand how policy actors influence the debate with political and scientific rhetoric in Ghana. The study reveals that in the midst of scientific uncertainties of Bt's potential for sustainable agriculture production and food security, policy decisions that encourage its future adoption are heavily influenced by health, scientific, economic, environmental and political factors dictated by different ideologies, values and norms. While locally pioneered plant breeding is visible and common in the Ghanaian food chain, plant breeding/GMOs/Bt from international corporations is strongly resisted by anti-GMO coalitions. Understanding the complex and messy nature of Bt policy-making is critical for future development of agricultural technology in Ghana and elsewhere.